2015
DOI: 10.1590/s0004-28032015000400004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection in Patients With Different Gastrointestinal Diseases From Northern Brazil

Abstract: -Background -The mechanisms whereby Helicobacter pylori produces different pathological manifestations in the stomach and duodenum are not fully understood. Considering the geographic diversity in the prevalence of virulence factors of this microorganism and their association with the development of different diseases, the search for pathogenicity markers such as CagA and VacA alleles by molecular techniques has intensified. Objectives -To investigate the presence of H. pylori infection and the frequency of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
1
21
1
12
Order By: Relevance
“…It is widely assumed that H. pylori can induce chronic active gastritis, both of which, in turn, can lead to the development of gastric cancer. Indeed, a high incidence of H. pylori infection was found recently in a cross-sectional study with 554 patients from Belém, mainly among patients with gastric ulcer and gastric cancer (4) .…”
Section: Introductionmentioning
confidence: 92%
“…It is widely assumed that H. pylori can induce chronic active gastritis, both of which, in turn, can lead to the development of gastric cancer. Indeed, a high incidence of H. pylori infection was found recently in a cross-sectional study with 554 patients from Belém, mainly among patients with gastric ulcer and gastric cancer (4) .…”
Section: Introductionmentioning
confidence: 92%
“…It presents as main reservoir the human stomach, colonizing its epithelium. Several studies have already demonstrated its relationship with gastrointestinal diseases, and the presence of the bacterium is a risk factor for chronic and atrophic gastritis, peptic ulcer disease, intestinal metaplasia, gastric adenocarcinoma and mucosal lymphoid tissue lymphoma (MALT) (1,2,3) .…”
Section: Introductionmentioning
confidence: 99%
“…After surviving in the stomach environment, flagellar motility is necessary to move the bacterium through the gastric epithelium cells. The interaction of H. pylori adhesins and cellular receptors supports gastric mucosa infection, and it is followed by the secretion of virulence factors (such as vacA, cagA, dupA and oipA genes) which cause tissue damage [1] [3] [4].…”
Section: Introductionmentioning
confidence: 99%